Meeting the demands of higher education: examining teaching and learning practices and academic challenges / Nurul Fitriah Alias and Rafiza Abdul Razak - Alias, Nurul Fitriah; Abdul Razak, Rafizan (Universiti Teknologi MARA, 2023)
This research paper investigates the current teaching and learning practices in higher education and the challenges faced by students. Higher education plays a vital role in personal and professional development, however, students often encounter various academic obstacles that impede their progress. The paper explores the causes of these challenges and proposes potential solutions, such as innovative teaching and learning approaches, that enhance student engagement and academic success. A comprehensive research methodology was used that employed quantitative and qualitative methods. A well-structured questionnaire was administered to 65 undergraduate students utilizing a 5point Likert scale to assess their perspectives. Additionally, in-depth interviews were conducted with a subset of five undergraduate students to gain deeper insights into the topic. The study's results indicate that the current teaching and learning practices are effective, as evidenced by the positive feedback from the students. They reported diverse teaching activities, including individual and group work, oral presentations, and research assignments. They also highlighted lecturers' encouragement of participating in class discussions and the fostering of an open communication and idea-sharing environment. These findings suggest that the current approach successfully engages students and promotes active learning. However, data analysis reveals seven primary learning challenges faced by students, including academic overload, time management, assignment burden, feeling overwhelmed, struggles with reading materials, extensive curricula, and short attention spans. These findings highlight the significant academic pressure on students and the need for increased support and resources to manage their workload effectively.